2019
DOI: 10.1186/s13017-019-0257-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of trauma-related emergency laparotomies, in an era of far-reaching specialization

Abstract: Background: Far reaching sub-specialization tends to become obligatory for surgeons in most Western countries. It is suggested that exposure of surgeons to emergency laparotomy after trauma is ever declining. Therefore, it can be questioned whether a generalist (i.e., general surgery) with additional differentiation such as the trauma surgeon, will still be needed and can remain sufficiently qualified. This study aimed to evaluate volume trends and outcomes of emergency laparotomies in trauma. Methods: A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 49 publications
6
15
1
1
Order By: Relevance
“…As a result, in the Netherlands the trauma surgeon treats both visceral injuries (neck/chest/abdomen/pelvis) and extremity injuries (including soft tissue injuries and fracture treatment) [2,3]. In addition, the trauma surgeon in the Netherlands has knowledge of physiological disturbances and cares for the resuscitation of the patient in the acute phase [4,5].…”
Section: The Dutch Systemmentioning
confidence: 99%
“…As a result, in the Netherlands the trauma surgeon treats both visceral injuries (neck/chest/abdomen/pelvis) and extremity injuries (including soft tissue injuries and fracture treatment) [2,3]. In addition, the trauma surgeon in the Netherlands has knowledge of physiological disturbances and cares for the resuscitation of the patient in the acute phase [4,5].…”
Section: The Dutch Systemmentioning
confidence: 99%
“…Kakande, et al (2001) intestinal obstruction represent the commonest indication for laparotomies [5]. Other authors however report that trauma associated with hemodynamic instability tops amongst the indications [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been conducted on the unplanned reop-eration rate in the field of trauma surgery. According to a study conducted by University Medical Center Utrecht in 2019, about 21% of patients undergoing abdominal trauma surgery underwent unplanned abdominal reoperations [10]; another level 1 Trauma Center reported a rate of roughly 20% [11]. A study conducted on unplanned abdominal reoperations after abdominal trauma surgery in the U.S. in 1978 [12] and a Russian study in 1985 [13] showed unplanned reoperation rates of 8.9% and 10.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%